Making mergers and acquisitions work : from strategy and target selection to post merger integration - Venzin, Markus; Vizzaccaro, Matteo; Rutschmann, Fabrizio (Directions in Development - Human Development., 2018)
This book addresses the salient question of how to make mergers and acquisitions work using a five-step approach. It explores insights gained from Prysmian's acquisitions and other prominent M & A deals, and compares them to existing best practices.